Literature Review: The Application of Problem Posing Models in Primary School Mathematics Learning (2020–2025) - Grace Sarira; Nanik Wijayati; Arif Widiyatmoko; Bambang Subali (Journal of Educational Sciences, 2026)
Mathematics learning in elementary schools continues to face challenges in strengthening students’ critical thinking, creativity, and active engagement. This study conducts a Systematic Literature Review (SLR) to analyze the implementation of the Problem Posing model in mathematics learning from 2020 to 2025, following the PRISMA stages of identification, screening, eligibility, and inclusion. A total of 25 national and international articles were reviewed based on publication year, context, research focus, and reported outcomes. The findings show that the Problem Posing model consistently improves students’ conceptual understanding, problem-solving skills, critical thinking, and creativity, while also enhancing motivation and active participation in learning. Its effectiveness increases when integrated with real-life contexts, digital media, and collaborative strategies that foster metacognitive reflection. Nonetheless, challenges such as limited instructional time, teacher readiness, and the absence of standardized creativity assessment tools remain. Overall, the evidence demonstrates that the Problem Posing model is an innovative and relevant approach aligned with the Independent Curriculum, offering strong potential for developing essential 21st-century competencies among elementary school students.